Effects of Paronychia kurdica on teat and udder papillomatosis in cows - Apaydin, A. M.; Aydin, M.; Ciftcl, O.; Timurkaan, N.; Yildiz, H.; Tonbak, S. (Ecole Nationale Veterinaire Toulouse, 2010)
The efficiency of Paronychia kurdica extract on teat and udder papillomatosis was investigated in 30 cows and heifers, which were randomly allotted in 5 equal groups. The plant extract was administered to animals orally at 2 dosages (5g and 10g, groups 1 and 2), subcutaneously (5g, group 3) or percutaneously as a pomade including 10% of Paronychia kurdica (group 4) whereas cows from the 5(th) group were untreated and served as negative controls. After a 90 day long experimental period, the proportions of completely cured animals (50% and 83.3%) were significantly more elevated when cows were orally or subcutaneously treated than in controls or in animals treated with the pomade. Furthermore, wart disappearance occurred earlier in these 3 groups (on days 5 and 10 vs. day 15 in groups 4 and 5) and was significantly intensified since the 15(th) day. In addition, wart losses were maximal in cows receiving oral treatment with 10g Paronychia kurdica extract. In parallel, high contents of unsaturated fatty acids (oleic and linoleic acids) and anti-oxidants (alpha-tocopherol, linol and linalool) were identified in the plant extract throughout gas chromatography and mass spectrometry. These results demonstrated beneficial effects of the Paronychia kurdica extract administered orally or subcutaneously on udder papillomatosis in cows but the identification of active compounds need further investigations.
Keywords: Papillomatosis; Paronychia kurdica; cow; udder; wart; remission